Simplified exercise test for the initial differential diagnosis of Pneumocystis carinii pneumonia in HIV antibody positive patients. Issue 2 (February 1994) - Sauleda, J; Gea, J; Aran, X; Aguar, M C; Orozco-Levi, M; Broquetas, J M
Abstract : BACKGROUND–This study was designed to evaluate the usefulness of a simplified exercise test in the differential diagnosis of Pneumocystis carinii pneumonia (PCP). METHODS–Forty five subjects with antibodies against the human immunodeficiency virus (HIV) and pneumonia were included and divided into two groups: those with PCP and those with "other pneumonias" (non-PCP). The test involved pedalling for two minutes on a stretcher bed and was considered positive if SaO2 decreased by at least 3%. RESULTS–During the exercise the mean(SE) SaO2 fell in patients with PCP from 88(4)% to 84(3)%, p < 0.01, whilst it improved slightly in subjects with non-PCP from 91(1)% to 93(3)%, p < 0.05. Sensitivity was 77% and specificity 91%. CONCLUSIONS–This simple test seems potentially useful for the initial investigation of HIV antibody positive patients with pneumonia.